Oncogenic Gα signaling requires AP-3-dependent recruitment to the endolysosomal compartment - Megha Shettigar; Salomé Moulière; Larissa Isenegger; Alexander L. DeVine; Cécile Gstalder; Vidyasagar Koduri; John G. Doench; Bruce Ksander; Mikel Garcia-Marcos; William G. Kaelin; Rizwan Haq (Proceedings of the National Academy of Sciences, 2026)
G protein–coupled receptors (GPCRs) constitute the largest superfamily of cell-surface receptors, yet the spatial constraints governing their signaling remain poorly defined. Here, we demonstrate that Gα, an essential downstream component of GPCR signaling, undergoes a spatial shift from the plasma membrane to the endolysosomal compartment upon its constitutive activation. Using a genome-wide CRISPR screen, we identify the adaptor protein AP-3 as the essential mediator of this trafficking event. Loss of AP-3-dependent recruitment impairs Gα-driven signaling and proliferation in uveal melanoma cells harboring oncogenic Gα mutations. We further identify a highly evolutionarily conserved AP-3 binding motif in all Gα proteins, present from yeast to humans. Disrupting this site causes Gα mislocalization and potently suppresses tumor growth and metastasis in vivo. Conversely, tethering Gα to the endolysosomal membrane is sufficient to rescue oncogenic signaling. Our findings reveal that endolysosomal recruitment is a fundamental, conserved requirement for Gα activity, uncovering a spatial vulnerability that may be exploited to target dysregulated G-protein signaling in human disease.